EFEKTIVITAS PEMBERIAN HYDROTHERAPI RENDAM KAKI PADA PENDERITA HIPERTENSI DI BANJAR SRI MANDALA, KELURAHAN DAUHWARU KABUPATEN JEMBRANA - N.L.G. Sudaryati; I P. Sudiartawan; Dwi Mertha Adnyana (UNHI Press, 2019)
The aim of the study was to determine the effectiveness of giving hydrotherapi foot soak in hypertensive patients. The study was conducted with one group pretestposttest design without a control group by measuring blood pressure (pretest) before being given an intervention in the form of foot soak hydrotherm against 15 people with hypertension in Banjar Sri Mandala, Dauhwaru Village, Jembrana Subregency. Then do the blood pressure measurement again (posttest) after finishing the intervention. After the study was completed, the results showed that before the hydrotherapi foot bath intervention, there were 0% of patients classified as normal, 13.32% in prehypertension category, 60.08% in hypertension category I and 26.60% in hypertension category II. After the intervention was given, there were 13.32% of the patients classified as normal, 66.68% in the prehypertension category, 20.00% in the first category of hypertension and no patients belonging to the second grade hypertension category. There is a decrease of 20-30 mmHg for systolic blood pressure and 0-10 mmHg for diastolic blood pressure after intervention. Based on the results of the study it can be concluded that the hydrotherapi foot bath is effectively used to reduce blood pressure in hypertensive patients in the Banjar Sri Mandala, Dauhwaru Village, Jembrana District.